EPIDEMIOLOGY, MANAGEMENT, AND ADMINISTRATIVE CHALLENGES OF DOG BITE CASES IN AN EMERGENCY OF A TERTIARY CARE HOSPITAL: A RETROSPECTIVE STUDY (2021–2023) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dog bite injuries remain a public health concern in India and contribute significantly to trauma, infection, and rabies risk. This study assessed the epidemiological profile, clinical management, and administrative challenges of dog bite injuries reported at a tertiary care hospital. Methods: A retrospective observational study was conducted in the Emergency Department of Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar. Medical records of 96 dog bite cases reported between January 2021 and December 2023 were reviewed. Data on demographics, incident characteristics, bite category, clinical management, and hospital stay were analysed descriptively. Results: Males comprised 67% of the sample. Children aged 0–5 years (36.5%) and adults over 60 years (16.7%) were the most affected groups. Stray dogs were responsible for 77% of bites. The face and head–neck region was the most commonly affected site (55.9%). All cases were Category III bites. Debridement and suturing were performed in 31% of cases, while 26% required grafting or flap procedures. General anaesthesia was required in 49% of cases. Delayed reporting (>24 hours) occurred in 17% of patients. Hospital stay of 1–2 days was recorded for 52% of cases. Conclusion: Dog bite injuries impose substantial clinical and administrative challenges, particularly in high-burden settings. The high proportion of severe bites, facial injuries, and surgical workload highlights the need for standardized triage pathways, improved public education, and coordinated animal control strategies.